Description and morphometry of the sting apparatus in the three worker casts of Acromyrmex subterraneus brunneus (Formicidae, Attini) - Camargo, Roberto S. [UNESP]; Forti, Luiz C. [UNESP]; De Matos, Carlos Alberto O. [UNESP]; Verza, Sandra S. [UNESP]; Fujihara, Ricardo T. [UNESP] (My University, 2007)
We studied the morphometry of the sting apparatus of Acromyrmex subterraneus brunneus workers by dissection and mounting of the structures on slides, and present here a brief description and illustrations. Sting apparatus examinations showed differences in size, but without morphological differences. The seven morphometric variables studied permitted grouping of the Ac. subterraneus brunneus workers into the following three groups: cluster 1 - consisting of 85, 39 large, 45 medium and 1 small workers; cluster 2 - consisting of 44 small workers, and cluster 3 - consisting of 6 large workers. This study demonstrated that all worker castes follow the same morphological pattern, although functional characteristics of the sting apparatus should be highlighted.
Keywords: Acromyrmex; Leaf-cutting ants; Sting apparatus; Worker; Acromyrmex subterraneus brunneus; Atta; Attini; Formicidae; Hexapoda